Tomenchuk M. V. Nationally marked concepts in modern canadian English - Tomenchuk M. V. (Philological Treatises, 2020)
The article focuses on the nationally marked concepts of the Canadian variety of Modern English as one of specific ways of their reality conceptualization. Main attention is paid to the description of verbalized concepts that form the core of Canadian nationally marked conceptual sphere and help to understand peculiarities of conceptualization of different objects, processes and phenomena in Canadian English.